Infraestruturas de transportes e desenvolvimento econômico: uma análise do modal rodoviário no estado de Sergipe - Nelson Fernandes Felipe Junior; Fabiana Santos Pinheiro (Confins)
This paper presents an analysis of road transport in the state of Sergipe, considering the economic impact, state planning, public and private investments and the existing bottlenecks. Investments in roads (although insufficient) contributed to the multiplier effect in Brazil, the Northeast region and Sergipe, especially between 2007 and 2013 (Growth Acceleration Program – PAC), which reflected the dynamization of some economic activities. Investments in transport infrastructures (mainly in the road modal) were/are relevant for economic development, with impacts on circulation, spatial interactions, productive activity, tertiary sector and others. Transport represents a historically strangled sector in Brazilian territory, demanding large public and private investments. In this sense, we highlight the proposal to change the concession model in force in Brazil and Sergipe, as well as the transportation of idle resources to the anti-idle sectors of the economy (infrastructure case).